A 'poly(ions–water ligand) network' electrolyte enables high-voltage high-conductivity aqueous metal-ion chemistries. Issue 42 (13th October 2022) - Qin, Tianfeng; Chen, Hao; Fang, Wenzhang; Cao, Guozhong; Gao, Chao
Abstract : A 'poly(ions–water ligand) network' electrolyte (PINE) is reported and indicates a wide electrochemical stability window of ∼4.6 V and a high ionic conductivity of ∼110 mS cm −1 at 25 °C. Abstract : Aqueous electrolytes are essential for ensuring safe and environmentally friendly energy storage devices. Low-concentration aqueous electrolytes exhibit narrow electrochemical stability windows (ESWs) of 1.23 V, but they have high ionic conductivities (∼125 mS cm −1 ). Contemporary methods use ultrahigh salt concentrations of 21–63 mol kg −1 (m), which can widen the ESWs (up to ∼3 V); however, they result in low ionic conductivities (10 mS cm −1 ). Achieving low-concentration aqueous electrolytes with wide ESWs and high ionic conductivities is challenging. Herein, we report a low-concentration aqueous electrolyte with a dual-network structure (2.11 m), a wide ESW of 4.6 V, and an ionic conductivity of 110 mS cm −1 at 25 °C. As a proof of concept, a 'poly(ion-water ligand) network' is designed to regulate the water properties of an 'ion/H2 O-rich hydrogen-bond network' (low-concentration aqueous electrolyte). Supercapacitors as well as zinc-ion capacitors exhibit excellent cycling stabilities and high energy densities (∼29 W h kg −1 and ∼128 W h kg −1, respectively) within the operating voltage window (0–2.5 V).